Analisis Sentimen Komentar Pengguna Info BMKG di Google Play Store - Lilis Yulia Fitriah; Muhammad Daffa Fauzan; Mohammad Raamdhan Ibnu Maulana (UIN Sunan Gunung Djati Bandung, 2024)
Climate change that is currently occurring is a challenge for every human being and even for the sustainability of the country. The impact of climate change is so great that it requires a preventive effort that can overcome or minimize the possibility of this impact occurring. Through optimizing the BMKG info application, it is hoped that the impact of climate change can be prevented because of the climatological information in it. Through a sampling of public comments on the BMKG info application, it is known what should be considered by the developer of this application in its optimization ranging from notifications, accuracy, regional coverage, to widgets.